Who Is the Successful University Student? An Analysis of Personal Resources - Stelnicki, Andrea M.; Nordstokke, David W.; Saklofske, Donald H. (Canadian Journal of Higher Education, 2015)
A number of factors have been identified in the research literature as being important for student success in university. However, the rather large body of literature contains few studies that have given students the opportunity to directly report what they believe contributes to their success as an undergraduate student. The primary purpose of this study is to explore students’ descriptions of the personal resources that they use to succeed while attempting to reach their goals as well as those personal characteristics or obstacles that keep them from reaching their goals. Prominent themes supportive of student success included having a future orientation, persistence, and executive functioning skills such as time management and organization. Results also demonstrate that stress, inadequate academic skills, and distractions are detrimental to student success in university. This study is unique in that it gathers the content data directly from the population of interest; it is one of the few qualitative studies of undergraduate students’ self-generated perceptions. Implications for university administrators and academic counsellors and directions for future research are discussed.